What interventions are effective to prevent or respond to female genital mutilation? A review of existing evidence from 2008-2020. - Dennis Juma Matanda; Nina Van Eekert; Melanie Croce-Galis; Jill Gay; Maria Johanna Middelburg; Karen Hardee (Public Library of Science (PLoS), 2023)
As the final decade of acceleration towards zero new cases of Female Genital Mutilation (FGM, SDG Target 5.3) by 2030 has begun, increasing the rigour, relevance, and utility of research for programming, policy development and resource allocation is critical. This study aimed to synthesize and assess the quality and strength of existing evidence on interventions designed to prevent or respond to FGM between 2008 and 2020.The study drew on a Rapid Evidence Assessment of the available literature on FGM interventions. The quality of studies was assessed using the 'How to Note: Assessing the Strength of Evidence' guidelines published by the Foreign, Commonwealth and Development Office (FCDO) and strength of evidence using a modified Gray scale developed by the What Works Association. Of the 7698 records retrieved, 115 studies met the inclusion criteria. Of the 115 studies, 106 were of high and moderate quality and were included in the final analysis. This review shows that at the system level, legislation-related interventions must be multifaceted to be effective. Whilst all levels would benefit from more research, for the service level especially more research is needed into how the health system can effectively prevent and respond to FGM. Community-level interventions are effective for changing attitudes towards FGM, but more must be done to innovate with these interventions so that they move beyond affecting attitudes alone to creating behaviour change. At the individual level, formal education is effective in reducing FGM prevalence among girls. However, the returns of formal education in ending FGM may take many years to be realized. Interventions targeting intermediate outcomes, such as improvement in knowledge and change in attitudes and beliefs towards FGM, are equally needed at the individual level.